The Influence of Economic Growth, Asset Turnover, Financial Risk on Stock Returns, with Business Risk as a Moderator in Property Companies Listed on the Indonesia Stock Exchange Period 2011-2016 - I Made Surya Dana (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
An economy is said to experience Economic expansion occurs when more goods and services are produced. In the real world, tracking how many units of products and services were created over a certain period of time is quite challenging. The disadvantage is evident not only because the types of goods and services produced are very diverse, but also the units of measure are different. because it is an estimated value. Gross Domestic Product figures show changes in Money is output value. GDP at constant prices is a measure of the gross domestic product (GDP) used to assess economic expansion